International education in practice : dimensions for national & international schools - Hayden, Mary; Thompson, J. J. (John Jeffrey), 1938-; Walker, George, Professor (Kogan Page ; Stylus Pub., 2002)
This book brings together present thinking on all aspects of international education, its management and the best practices.